The Reserve Officer Training Unit and Soft Skills - Shariffuddin, Mohd Dino Khairri; Ahmad Apandi, Laila Suriya; Ayub, Zainal Amin; Wallang, Muslimin; Saad, Ram Al Jaffri; Sagena, Uni W. (2022)
This paper examines ROTU cadets and soft skills. It argues that being a ROTU cadet could enhance his/her soft skills. This further posits good employability potentials of a ROTU cadet Furthermore, most employers prefer to hire graduates with excellent soft skills. The finding found that majority of the ROTU cadets believe being a ROTU cadet could enhance his/her soft skills